Gender bias experiences among rural adolescent girls - Ade, Anju Damu; Rao, G. Visweswara; Manyam, M. Sunitha (International Journal Of Community Medicine And Public Health, 2022)
Background: Girls in India are disadvantaged even before their birth. For a girl child, life is a constant fight for survival, growth and development from the time she is conceived till she attains 18 years. Objectives were to study the socio-demographic profile of the rural adolescent girls to study gender bias experiences among rural adolescent girls and to assess association between sociodemographic characteristics and gender bias. Methods: A cross sectional study was conducted in three secondary rural government schools among rural adolescent girls in the age group of 12 to 16 years. Study participants were interviewed. Results: Total respondents were 157.29 (18.5%) said they don’t get immediate treatment for their health issues. The 153 (97.5%) respondents said their parents support them for their education. The 12 (7.6%) girls said their parents ask them to eat food after males in their families.145(92.45%) didn’t find any discrimination regarding food with them. The 92 (58.6%) said parents force them to do domestic work. The 87 (55.4%) of the respondents said relatives ask them to sit properly and not according to their comfort. Only 19 (12.1%) said parents tell them to do puja regularly and keep fasting for religious reasons. The 88 (56.1%) respondents said that they have restrictions in going out. The 51 (32.5%) respondents said they have been verbally abused or beaten. Conclusions: Gender bias still exists among rural community. It is critical to intervene during early adolescence if gender equity is to be established. Promoting gender equality and empowerment of girls will help to diminish gender inequity in the long-term.